Extracurricular management and student learning motivation: a comparative study of senior high schools in indonesia - Supatmin; Ayi Najmul Hidayat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the effectiveness of extracurricular activity management in enhancing students’ learning motivation through a comparative analysis of two educational approaches, using the Plan-Do-Check-Act (PDCA) cycle framework and Self-Determination Theory. A comparative descriptive qualitative study was conducted at SMA Negeri 5 South Tangerang (conventional school) and SMA Dharma Karya Open University (open education system) during July–September 2025. Data were collected through in-depth interviews, participatory observations, and document analysis involving 45 participants, including principals, extracurricular coordinators, supervisors, and students. The findings indicate that both schools positively influenced students’ motivation with distinctive characteristics: the conventional school achieved higher participation (85%) and better academic performance (average 84.2 vs. 78.6), while the open system school, despite lower participation (45%), fostered stronger intrinsic motivation and higher quality motivational scores. These results highlight that PDCA-based management, when adapted to institutional contexts, is a key factor for developing sustainable and responsive extracurricular programs that optimize students’ learning motivation